Structure Design of Long‐Life Spinel‐Oxide Cathode Materials for Magnesium Rechargeable Batteries. Issue 7 (18th January 2021) - Shimokawa, Kohei; Atsumi, Taruto; Okamoto, Norihiko L.; Kawaguchi, Tomoya; Imashuku, Susumu; Wagatsuma, Kazuaki; Nakayama, Masanobu; Kanamura, Kiyoshi; Ichitsubo, Tetsu
Abstract: Development of metal‐anode rechargeable batteries is a challenging issue. Especially, magnesium rechargeable batteries are promising in that Mg metal can be free from dendrite formation upon charging. However, in case of oxide cathode materials, inserted magnesium tends to form MgO‐like rocksalt clusters in a parent phase even with another structure, which causes poor cyclability. Here, a design concept of high‐performance cathode materials is shown, based on: i) selecting an element to destabilize the rocksalt‐type structure and ii) utilizing the defect‐spinel‐type structure both to avoid the spinel‐to‐rocksalt reaction and to secure the migration path of Mg cations. This theoretical and experimental work substantiates that a defect‐spinel‐type ZnMnO3 meets the above criteria and shows excellent cycle performance exceeding 100 cycles upon Mg insertion/extraction with high potential (≈2.5 V vs Mg 2+ /Mg) and capacity (≈100 mAh g −1 ). Thus, this work would provide a design guideline of cathode materials for various multivalent rechargeable batteries. Abstract : Defect spinel ZnMnO3 with cation deficiencies at octahedral sites allows highly reversible Mg insertion/extraction avoiding the irreversible transformation into a rocksalt phase. It is successfully demonstrated that the material can work as a high‐performance cathode for magnesium rechargeable batteries exhibiting high potential (≈2.5 V vs Mg 2+ /Mg) and capacity (≈100 mAh g −1 ) with long‐term cyclability.